PENGARUH INFORMASI AKUNTANSI DALAM KEBIJAKAN PENGAMBILAN KEPUTUSAN KEUANGAN PT. INCIPNA INDONESIA MAKASSAR - Faidul Adziem; Idra Wahyuni; Sarman Sarman (Jurnal Riset Perpajakan: Amnesty, 2018)
Research aims to determine the influence of accounting information in the financial decision making policy of PT. Incipna Indonesia Makassar. The object of the study's financial management income, the instrument in the study was through kuesiner to the parties concerned. The research also collects the relevant documents and supports the discussion of the research. The testing techniques used are simple linear regression. The results found that the accounting information was influential in the financial decision making policy of PT. Incipna Indonesia Makassar. In formulating financial policies, consider the vision, mission, objectives, and objectives so that each policy is made.